(untitled) (International Journal of Built Environment and Sustainability, 2022)
The changing lifestyle, urbanization, and depletion of non-renewable resources to match the ever-increasing energy demand are causing a pessimistic impact on the environment. The cities are responsible for 75% of carbon emissions and about 60-80% of the energy consumption globally, causing a precarious situation because they only constitute 3% of the earth’s land. Urbanization makes the cities vulnerable due to the changing climatic conditions and possibilities of natural deserts disasters, thereby compelling the researchers to go for planning building green and resilient cities. Green cities are imperative in resisting the environmental crisis and assure a sustainable future for the upcoming generations. The pivotal role for the green cities is played by the renewable sources of energy. Therefore, solar and wind energy systems were employed, but eventually these renewable energy systems are associated with cost and pollution issues. This led to the paradigm-shifting towards algae as a third-generation feedstock and it is expected to become a potential source of green energy and environment due to the following advantages: (i) sequestration of CO2 and other greenhouse gases (GHGs), (ii) they can be easily and rapidly cultured and bioengineered, (iii) they can utilize the wastewater as a source of nutrients for its cultivation, (iv) their growth does not depend upon the geography and climate, and (v) algal biomass can be processed into biofuels (biodiesel, bioethanol, biogas etc) and other useful bioproducts (biofertilizer & biochar). This review paper incorporates the role of microalgal bioreactive façades (algae powered buildings) in the simultaneous mitigation of environment and energy production, contributing to green cities. Since the importance of Urban Green Space (UGS) is imperative for green cities, its functions and role during the critical period of the pandemic are also explained together with the efficient and viable biofoundry approach of converting algal blooms in urban water bodies to energy and useful products.